ENERGY EFFICIENCY IMPROVEMENT PLAN - Matulis, Jānis; Teirumnieka, Ērika (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
As climate change issues and increasing CO2 emissions are rising, "green energy" or renewable energy sources include solar, wind power, biomass, geothermal energy, etc. One of the most important sectors of the economy is energy. Its main tasks are energy recovery, its processing in all types of energy and delivery to consumers. No energy development is possible without the development of any economic sector. Energy is mainly used for energy production